2012
DOI: 10.1038/bjc.2011.597
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases free survival differs between breast cancer subtypes

Abstract: Background:Brain metastases (BM) are frequently diagnosed in patients with HER-2-positive metastatic breast cancer; in addition, an increasing incidence was reported for triple-negative tumours. We aimed to compare brain metastases free survival (BMFS) of breast cancer subtypes in patients treated between 1996 until 2010.Methods:Brain metastases free survival was measured as the interval from diagnosis of extracranial breast cancer metastases until diagnosis of BM. HER-2 status was analysed by immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 30 publications
4
79
2
Order By: Relevance
“…This variable 18 F-FET uptake might be attributed to different malignant melanoma metastasis subtypes, for example, amelanotic melanoma histology, which could not be assessed in all cases because of the missing histopathologic confirmation. Furthermore, general heterogeneity of brain metastases could be discussed as cause as well (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…This variable 18 F-FET uptake might be attributed to different malignant melanoma metastasis subtypes, for example, amelanotic melanoma histology, which could not be assessed in all cases because of the missing histopathologic confirmation. Furthermore, general heterogeneity of brain metastases could be discussed as cause as well (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported lower 15-year cumulative incidence rates of brain metastases among patients with luminal subtype breast cancer, whereas those with HER2 positive/hormone receptor negative disease and those with basal-like tumors had higher rates of 14.3% and 10.9%, respectively. Berghoff and colleagues [27] recently reported on the interval from the diagnosis of extracranial metastases to the development of brain metastases stratified by breast tumor subtype in a cohort of 213 women with metastatic breast cancer between 1996 and 2010. The authors reported a brain metastases-free survival of 14, 18, and 34 months among patients with triple negative, HER2-positive, and luminal tumors, respectively.…”
Section: The Influence Of Breast Cancer Subtypementioning
confidence: 99%
“…Young age, high histologic grade, and tumour subtype are major risk factors [3,4]. BM are usually confirmed radiologically with magnetic resonance imaging (MRI), with or without gadolinium contrast enhancement, in patients who develop neurological symptoms (e.g., chronic headache, motor, cognitive or speech deficits, and seizures).…”
Section: Clinico-epidemiologic Profile Of Brain Metastatic Breast Cancermentioning
confidence: 99%